A study on glycemic control among insulintreated type 2 diabetes patients attending diabetes centre, HUSM, Kelantan - Haryati, Hamzah (2009)
The goal in management of Type 2 Diabetes Mellitus is to achieve control of HbAlc. Unfortunately, many patients with diabetes unable to achieve glycemic target Due to this, combination insulin and oral anti-diabetic agent or full dose insulin is an alternative in order to improve the glycemic control. Emerging data indicates that the addition of insulin able to improve HbAlc and reduce the risk of micro and macrovascular diabetes The study was conducted to examine the percentage good glycemic control among insulintreated T2DM patients and to study the factors that contribute to good glycemic control. lbis is s cross sectional study. In this survey a set of case report form (CRF) or proforma was completed by 236 insulin-treated T2DM patients attended Diabetic clinic AND Klinik Rawatan Keluarga, HUSM from January 2008 until November 2008. The CRF was divided into 2 sections. The section 1 consists of sociodemographic data while the section 2 comprised of background history of diabetes and clinical characteristics that was filled up,by the researcher by reviewing the patients' case notes The result showed that the percentage of good glycemic control of insulin-treated diabetes patients was 21.2% and the factors that contribute to good glycemic control were female gender, high education, combination of insulin and OAD regime, basal bolus insulin and fasting blood sugar. Factors that were found to be protective towards good glycemic control include financial support by the patient and the partner, high LDL-C, high TC and non-obese. In conclusion, good glycemic control among insulin-treated T2DM attending the Diabetes Center, HUSM is still low. This study found out that only 21.2% of T2DM on insulin therapy achieved good glycemic control according to ADA recommendation. Factors that contribute to good glycemic control were female gender, high education, combination of insulin and OAD regime, basal bolus insulin and fasting blood sugar. Factors that were found to be protective towards good glycemic control include financial support by the patient and the partner, high LDL-C, high TC and non-obese. Assessment of glycemic control should be a routine during follow-up. By recognizing the factors that contribute to good glycemic control will help the health care provider to plan an intervention program to improve glycemic control and subsequently reduce the cost treating the disease and its complications.